Learning Community: A Case Study of Taman Pendidikan Masyarakat Tanyo (TPMT), Aceh Besar - Tathahira Tathahira (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Taman Pendidikan Masyarakat Tanyoe (TPMT) becomes one of examples of how education is still progressing in the heart of rural community in Aceh Besar sub-district in Aceh Province. As learning community in rural area, TPMT faced some challenges in order to regain their existence in the midst of modern learning environment. This case study attempted to see how TPMT preserved their existence as learning community through some strategies in order to serve the community in Lambirah, Aceh Besar. The data were collected through observation, interview and documents. The findings revealed that there were two essential steps needed by TPMT to resolve the issues, namely maintaining the “active relationship” (based on the Social Capital principle); overcoming the issues related to the self and teaching development experienced by permanent and volunteered staff; and utilising the natural potency of Lambirah village and TPMT as the learning community to direct and gain attention from the local policy maker. This case study essentially shared a valuable lesson of being Social Capital actors to the renewal and sustainability of a community.